2010
DOI: 10.1002/asia.201000438
|View full text |Cite
|
Sign up to set email alerts
|

The Design of α/β‐Peptides: Study on Three‐Residue Turn Motifs and the Influence of Achiral Glycine on Helix and Turn

Abstract: Novel three-residue helix-turn secondary structures, nucleated by a helix at the N terminus, were generated in peptides that have 'β-Caa-L-Ala-L-Ala,' 'β-Caa-L-Ala-γ-Caa,' and 'β-Caa-L-Ala-δ-Caa' (in which β-Caa is C-linked carbo-β-amino acid, γ-Caa is C-linked carbo-γ-amino acid, and δ-Caa is C-linked carbo-δ-amino acid) at the C terminus. These turn structures are stabilized by 12-, 14-, and 15-membered (mr) hydrogen bonding between NH(i)/CO(i+2) (i+2 is the last residue in the peptide) along with a 7-mr hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The use of diverse β‐amino acids led to a range of helical structures that have been enlarged with α/β‐hybrid peptides containing different mode of combinations of α and β residues. However, in this last case a limited set of examples have been reported that can be divided in two groups, namely oligomers with repetitive 2:1, 1:2, or 2:2 α:β patterns, or oligomers with an aperiodic α/β sequence . Interestingly, oligomers involving a trans ‐ACPC residue with 2:1 or 1:2 α/β residue patterns adopted distinctive helical structures with the coexistence in each case of two helical forms in solution, whereas in crystal structures only a 10/11/11‐ and a 11/11/12‐helix were observed, respectively .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The use of diverse β‐amino acids led to a range of helical structures that have been enlarged with α/β‐hybrid peptides containing different mode of combinations of α and β residues. However, in this last case a limited set of examples have been reported that can be divided in two groups, namely oligomers with repetitive 2:1, 1:2, or 2:2 α:β patterns, or oligomers with an aperiodic α/β sequence . Interestingly, oligomers involving a trans ‐ACPC residue with 2:1 or 1:2 α/β residue patterns adopted distinctive helical structures with the coexistence in each case of two helical forms in solution, whereas in crystal structures only a 10/11/11‐ and a 11/11/12‐helix were observed, respectively .…”
Section: Figurementioning
confidence: 99%
“…However,i nt his last case al imited set of examples have been reported that can be divided in two groups,n amely oligomers with repetitive 2:1, 1:2, or 2:2 a:b patterns, [17][18][19][20] or oligomers with an aperiodic a/b sequence. [21][22][23] Interestingly, oligomers involving a trans-ACPC residue with 2:1o r1 :2 a/ b residue patterns adopted distinctive helical structuresw ith the coexistence in each case of two helical formsi nsolution, whereasi nc rystal structures only a1 0/11/11-and a1 1/11/12helix were observed, respectively. [17,18] More recently,f ollowing the proposed stereochemical patterning approach, [19] Martinek and Reiser demonstrated that a2:2 alternation of cis-ACPC and a-amino acids motifs resultedi nastable 9/12/9/12-helical structure.…”
mentioning
confidence: 99%
“…Interestingly, this turn was akin to the α turn that involved five residues and hydrogen bonds that have the same directionality. Later studies15b by our group have shown that the turn in HT motifs initiated by a α/β helix can accommodate a wide variety of turns, such as ‘β‐α‐α’, ‘β‐α‐γ’, and ‘β‐α‐δ’, in which α, β, γ, and δ refer to α‐, β‐, γ‐, and δ‐amino acids, respectively. These turns were stabilized by 12‐, 14‐, and 15‐member hydrogen bonds (NH( i −2) ⋅⋅⋅ CO( i ), with i being the last residue at the C terminus) and a 7‐member hydrogen bond (CO( i −2) ⋅⋅⋅ NH( i )), respectively 15b.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies15b by our group have shown that the turn in HT motifs initiated by a α/β helix can accommodate a wide variety of turns, such as ‘β‐α‐α’, ‘β‐α‐γ’, and ‘β‐α‐δ’, in which α, β, γ, and δ refer to α‐, β‐, γ‐, and δ‐amino acids, respectively. These turns were stabilized by 12‐, 14‐, and 15‐member hydrogen bonds (NH( i −2) ⋅⋅⋅ CO( i ), with i being the last residue at the C terminus) and a 7‐member hydrogen bond (CO( i −2) ⋅⋅⋅ NH( i )), respectively 15b. Further studies on peptides with a ‘β‐α‐β’ C‐terminal sequence that have Gly as the α residue instead of L ‐Ala showed that the turn was stabilized only by a 13‐member hydrogen‐bonded pseudoring,15b whereas the 7‐member hydrogen bond was conspicuously absent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation